2022
DOI: 10.3389/fnut.2022.847215
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Exercise Training and Nutritional Supplementation in Cancer Patients in the Context of the COVID-19: A Perspective Study

Abstract: The 2019 coronavirus (COVID-19) epidemic, has caused unprecedented global social and economic impacts and many deaths. Many risk factors have been identified in the progression of COVID-19 to severe and critical stages, and it is shown that the coronavirus appears more severely in people with cancer. Pro-inflammatory status and weakened immune system due to cancer-related treatments can be determinants in the immune system’s response to the coronavirus in these patients. Higher physical activity levels are ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 91 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…It's also important steps by the prioritization of oncological surgical care and the allocation of resources during the COVID-19 pandemic 73 . In addition, lifestyle modification (dietary supplementation and regular physical exercise) is effective in treatment outcomes, quality of life, and overall survival in cancer patients with COVID-19 74 . Moreover, clinical decision support systems 75 and web-based lifestyle interventions 76,77 for cancer survivors are a promising treatment option due to being both affordable and accessible.…”
Section: Novel Strategies For Management Of Cancer In the Covid-19 Eramentioning
confidence: 99%
“…It's also important steps by the prioritization of oncological surgical care and the allocation of resources during the COVID-19 pandemic 73 . In addition, lifestyle modification (dietary supplementation and regular physical exercise) is effective in treatment outcomes, quality of life, and overall survival in cancer patients with COVID-19 74 . Moreover, clinical decision support systems 75 and web-based lifestyle interventions 76,77 for cancer survivors are a promising treatment option due to being both affordable and accessible.…”
Section: Novel Strategies For Management Of Cancer In the Covid-19 Eramentioning
confidence: 99%
“…Several studies were published emphasizing staying active to improve the immune system (18,(22)(23)(24). Further studies reported low intensity training (LIT) to moderate intensity training (MIT) home-based exercise can improve the functioning of the antioxidant system and the immune system (18,25,26). Despite the recommendations for the population to remain physically active, the level of physical activity decreased significantly in the coronavirus outbreak (27).…”
Section: Increase Physical Activity To Counteract Omicron Disseminationmentioning
confidence: 99%
“…It seems that low-and moderate-intensity sports activities have favorable effects on the immune system in dealing with COVID-19 by modulating the lymphocytes, pro-inflammatory and inflammatory cytokines, and regulating the expression of interferon 1 (33). So physical exercise should be commensurate with the nature of COVID-19 to prevent recurrence of infection or impaired immune function (26,30,34). It is recommended that children and adolescents between 5 and 17 years perform MIT (60 minutes, about 70% of heart rate maximum, three sessions per week) (35).…”
Section: Increase Physical Activity To Counteract Omicron Disseminationmentioning
confidence: 99%